Deintensification of Adjuvant Treatment After Transoral Surgery in Patients With Human Papillomavirus-Positive Oropharyngeal Cancer: The Conception of the PATHOS Study and Its Development - Hargreaves, Sarah; Beasley, Matthew; Hurt, Chris; Jones, Terry M.; Evans, Mererid (Frontiers in Oncology, 2019)
PATHOS is a phase II/III randomised controlled trial (RCT) of risk-stratified, reduced intensity adjuvant treatment in patients undergoing transoral surgery (TOS) for human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma (OPSCC). The study opened in the UK in October 2015 and, after successful recruitment into the phase II, transitioned into phase III in the autumn of 2018. PATHOS aims to establish whether the de-intensification of adjuvant treatment in patients with favourable prognosis HPV-positive OPSCC will confer improved swallowing outcomes, whilst maintaining high rates of cure. In this article, we will outline the rationale for the study and how it aims to answer fundamentally important questions about the safety, effectiveness and functional outcomes of minimally invasive TOS techniques followed by adjuvant radiotherapy (RT) or chemo-radiotherapy (CRT) in this patient population.